Analisis Nilai-Nilai Profil Pelajar Pancasila pada Film G30S/PKI untuk Anak Sekolah Dasar - Ristiani, Elsa; Wardana, M. Yusuf Setia; Purnamasari, Iin (CV. Supernova Office Stationary and Printing, 2022)
The background that drives this research is the low grades of Pancasila students in elementary school age children. It is hoped that the G3OS/PKI film by Arifin C Noer can be a reference for Pancasila students through an innovative and fun way by watching to increase the value of Pancasila students at elementary school age. This type of research is a qualitative research with descriptive analysis. The data in this study were obtained through interviews, documentation, and observation and recording methods. The results of the analysis are that the G30S/PKI film contains six values ??of the Pancasila Student Profile, namely Faith and piety to God Almighty, and noble character, Global Diversity, Mutual Cooperation, Independent, Critical Reasoning, and Creative. The six values ??of Pancasila students appear in the description of the scenes and actions taken by the film characters. Of the six values ??of Pancasila lessons, the value of Critical Thinking is the value that often appears in the G30S/PKI film. The G30S/PKI film is based on a total analysis that includes all the values ??of Pancasila students which is used as a reference and the results of interviews with school principals, sixth grade teachers and sixth grade students, the G30S/PKI film deserves to be used as an example for the audience, especially children and the application of student grades Pancasila in everyday life.